Periodontitis patients’ oral health experience and quality of life during the Malaysian Movement Control Order-2020 - Nor Adila Mohd-Norwir,; Seah Ke Xin,; Lee Rhea Meisha,; Tuti Ningseh Mohd-Dom,; Shahida Mohd-Said, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The coronavirus disease 2019 (COVID-19) has sparked concerns among dental patients due to its high infectivity. The implementation of the Movement Control Order in 2020 by the Malaysian government (MMCO-2020) has added constraints to access to dental clinics and may affect the patients’ status of oral disease. This study aims to investigate the impact of MMCO-2020 on the periodontal health and oral health-related quality of life (OHRQoL) of periodontitis patients with/out non-communicable diseases (NCDs). A cross-sectional study involving 139 patients with periodontitis was conducted to assess patients’ OHRQoL, oral health problems, and their perceived barriers to access dental treatment during MMCO-2020 using the Oral Health Impact Profile (OHIP-14) and questionnaire on oral health-related problems. The overall mean OHIP-14 score was relatively low (10.08 ± 8.861), suggesting that the OHRQoL is generally good during MMCO-2020. However, 44 (31.7%) periodontitis patients score ADD ≥14, indicating poorer oral health status and greater dental treatment needed. There was statistically significant association between periodontitis patients with comorbidities (i.e., presence of NCDs) with poorer OHIP-14 scores and mean plaque score changes at pre- and postMMCO, suggesting that special care is required by this group, even during the national lockdown. Of the 45 (32.4%) patients who reported having problems, most (30, 36.1%) decided to “visit the dentist for treatment’. Meanwhile, the most frequent barriers were “could not get an appointment” (14, 34%), “problem is not serious” (13, 39.4%) and “fear of COVID” (9, 27.3%). The MMCO-2020 restrictions on the population had a minimal negative impact on the OHRQoL of patients with periodontal disease, but provisions can be arranged to address the basic and urgent needs of selected periodontitis patients, especially those presented with medical comorbidities.